PENGEMBANGAN NANOPARTIKEL EKSTRAK TEMULAWAK (Curcuma xanthorrhiza, Roxb) DENGAN TEKNIK SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) MENGGUNAKAN FASE MINYAK IKAN CUCUT BOTOL (Centrocymnus crepidater) SEBAGAI OBAT ANTIINFLAMASI - , SEPTIANA INDRATMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Curcuma xanthorrizha is an herbal which is safe to be used for the treatment of inflammation because its curcumin compounds. The use of curcumin for treatment are limited because of its low solubil ity in water and produce minimal systemic bioavailability. A method that may be applied to the formulation of Curcuma xanthorrizha extract is the method of SelfNanoemulsifying Drug Delivery System (SNEDDS) using shark liver oil. This study was conducted to determine the effect of formulation SNEDDS on characteristics of Curcuma xanthorrizha extract and its effect of antiinflammatory effects. In this study, SNEDDS Curcuma xanthorrizha extract was formulated with shark liver oil, and a surfactant, co -surfactant selected. Nanoemulsion was tested on its particle size, zeta potential, drug loading, emulsification time, stability, and dissolution. The effect of antiinflammatory activity was tested in rats. SNEDDS Curcuma xanthorrizha extract could be generated by a formula tween 80, PEG 400 and shark liver oil with a ratio of 5: 1: 1. Particle size of nanoemulsion that was resulted is 126.8 nm, zeta potential value of +20.78 mV, drug loading 100 mg/mL, emulsification time was 18.72 seconds and stability nanoemulsion was 6 h in artificial gastric fluid (AGF). The dissolution profile of SNEDDS Curcuma xanthorrizha extract was better than Curcuma xanthorrizha extract. Antiinflammatory effect of SNEDDS Curcuma xanthorrizha extract was greater than Curcuma xanthorrizha extract in mice. SNEDDS Curcuma xanthorrizha extract at the dose of 50 mg/kg bw showed greater anti-inflammatory effect than 12.5 mg/kg bw and 25 mg/kg bw of SNEDDS Curcuma xanthorrizha extract.